Peran Kepercayaan Dalam Mediasi Hubungan Antara E-Servicescape Dan Repurcase Intention : Aplikasi Halodoc - Wulandari, Yulia Tri; Hayadi, Ilsya (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This research aims to examine the influence of e-servicescape (aesthetic appeal, layout and functionality and financial security) on repurchase intention through trust in the halodoc application. The data used is primary data. This research is included in quantitative research using purposive sampling techniques. The population of this research is all people who have used the Halodoc application, totaling 200 respondents. This research uses SEM-PLS version 4.0. The results of this research showed that aesthetic appeal, layout and functionality and financial security had a significant positive effect on trust and repurchase intention, then that aesthetic appeal, layout and functionality and financial security also had a significant positive effect on repurchase intention through trust.